2019
DOI: 10.1371/journal.pone.0214261
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific effects of facial dominance and trustworthiness on hypothetical leadership decisions

Abstract: Social judgments of faces predict important social outcomes, including leadership decisions. Previous work suggests that facial cues associated with perceptions of dominance and trustworthiness have context-specific effects on leadership decisions. Facial cues linked to perceived dominance have been found to be preferred in leaders for hypothetical wartime contexts and facial cues linked to perceived trustworthiness have been found to be preferred in leaders for hypothetical peacetime contexts. Here we sought … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…They found that participants had a stronger preference for individuals whose facial trustworthiness had been digitally enhanced in a time of peace, whereas individuals whose facial attractiveness had been digitally enhanced were more strongly favored in a time of war. This pattern suggests that prosocial traits (i.e., trustworthiness) are favored in leaders when the political context is characterized by collaboration, but traits related to health and formidability (i.e., attractiveness) are favored when the political climate is characterized by conflict (for similar results, see Ferguson et al, 2019;Laustsen & Petersen, 2015;Spisak et al, 2012).…”
Section: Election Context Moderates Trait Preferencesmentioning
confidence: 82%
“…They found that participants had a stronger preference for individuals whose facial trustworthiness had been digitally enhanced in a time of peace, whereas individuals whose facial attractiveness had been digitally enhanced were more strongly favored in a time of war. This pattern suggests that prosocial traits (i.e., trustworthiness) are favored in leaders when the political context is characterized by collaboration, but traits related to health and formidability (i.e., attractiveness) are favored when the political climate is characterized by conflict (for similar results, see Ferguson et al, 2019;Laustsen & Petersen, 2015;Spisak et al, 2012).…”
Section: Election Context Moderates Trait Preferencesmentioning
confidence: 82%
“…A long line of evidence shows that use of facial cues as a heuristic does occur. This effect is most strongly evident in the case of voting in elections (Antonakis & Dalgas, 2009;Berggren et al, 2010;Berinsky et al, 2019;Bull et al, 1983;Chiao et al, 2008;Ferguson et al, 2019;Lawson et al, 2010;Little et al, 2007;Rosar et al, 2008;Todorov et al, 2005Todorov et al, , 2015Van Vugt & Grabo, 2015). There is also evidence that this effect manifests, albeit to a lesser degree, when selecting individuals for administrative leadership positions (Fruhen et al, 2015;Linke et al, 2016;Mazur et al, 1984;Mazur & Mueller, 1996;Mueller & Mazur, 1996a).…”
Section: Facial Traits In Policing Promotionsmentioning
confidence: 99%
“…Though Kahneman identifies many System 1 heuristic types, we focus our study on the phenomenon of leadership selection based on an individual's facial traits. Humans use facial traits to make judgments about competence (Antonakis & Dalgas, 2009;Todorov et al, 2005), trustworthiness (Linke et al, 2016), intelligence, honesty (Bull et al, 1983), and dominance (Berinsky et al, 2019;Bull et al, 1983;Chiao et al, 2008;Ferguson et al, 2019;Fruhen et al, 2015). These judgments correlate with perceived leadership ability and with assessments of candidate leadership potential (Van Vugt & Grabo, 2015) such that human leadership choices can often be predicted based on particular facial image cues (Mazur et al, 1984;Mazur & Mueller, 1996;Mueller & Mazur, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, facial judgments of trustworthiness and dominance of political candidates positively predicted intent to vote for those candidates (Little et al, 2012). During times of conflict, more dominant-faced people were preferred for leadership positions (Ferguson et al, 2019). Dominant faces are also motivationally salient, eliciting attention to highly dominant faces (Wang et al, 2016).…”
Section: Trustworthiness and Dominancementioning
confidence: 99%